2013
DOI: 10.1016/j.rboe.2012.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and its Relation to Bone Mineral Density in Postmenopause Women

Abstract: Objective Compare the level of vitamin D with the bone mineral density (BMD) in postmenopausal women, with or without fractures. Methods 250 women with mean age of 71.1 were evaluated. The serum levels of vitamin D considered sufficient were ≥ 30 ng/mL, insufficient between 20 and 30 ng/mL and deficient < 20 ng/mL. The bone mineral density was measured and considered osteopenia when T value total of lumbar spine or hip was between -1 and -2.5 and osteoporosis < 2.5. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 37 publications
2
7
0
2
Order By: Relevance
“…Though literature widely reports positive association between BMD and Vitamin D [ 56 ], our data set of population uncovered finding of no relationship between the two. However similar findings have been reported by other colleagues too [ [57] , [58] , [59] , [60] ]. The conflicting findings can partially be elucidated by ethnic differences in the populations and wider age groups (20–80 years).…”
Section: Discussionsupporting
confidence: 92%
“…Though literature widely reports positive association between BMD and Vitamin D [ 56 ], our data set of population uncovered finding of no relationship between the two. However similar findings have been reported by other colleagues too [ [57] , [58] , [59] , [60] ]. The conflicting findings can partially be elucidated by ethnic differences in the populations and wider age groups (20–80 years).…”
Section: Discussionsupporting
confidence: 92%
“…As seen in the results presented above, women were found to have lower levels of VD in both groups of patients, indicating an increased incidence of hypovitaminosis D in the female sex. Many studies have confirmed this fact [24], as women have a gradual decline in postmenopausal VD levels and aging intensifies the hypovitaminosis. A large study with a 90,000-women sample revealed an increased incidence of hypovitaminosis D and increased risk for hip fracture [25].…”
Section: Discussionmentioning
confidence: 86%
“…In the present study, serum vitamin D levels were comparable between the non-osteoporotic and osteoporotic groups. Similarly, few other studies demonstrated no significant difference in mean values of vitamin D between control and osteoporosis postmenopausal women ( 12 , 13 ). In contrast to our results, several studies have reported significantly lower levels of Vitamin D among osteoporotic postmenopausal women compared to the control group ( 14 , 15 ).…”
Section: Discussionmentioning
confidence: 80%